Effect of Shentongzhuyu Decoction on p38MAPK Signal Pathway in Annulus Fibrosus Cells of Model Rats with Lumbar Disc Degeneration - Sha CHEN; Shizhong WANG; Dewan DENG (康复学报)
Objective:To explore the effect of Shentongzhuyu decoction on p38MAPK signal pathway in annulus fibrosus cells of model rats with lumbar disc degeneration.Methods:A total of 24 male adult SD rats were randomly divided into Shentongzhuyu decoction group, model group and sham-operated group. Models of lumbar disc degeneration were established in rats of Shentongzhuyu decoction group and model group with the method of puncturing the anulus fibrosus with needles. Then after one month, Shentongzhuyu decoction group received Shentongzhuyu decoction by gavage, and model group and sham-operated group received normal saline once daily for four weeks. After the treatment, the rats were killed and lumbar disc tissues were taken out. The protein expressions of p-p38, p38 and NF-κB were observed and detected by Immunohistochemistry and Western Blot.Results:The protein expressions of p-p38 and NF-κB in Shentongzhuyu decoction group were lower than those of model group respectively (P<0.05), and the protein expressions of p-p38 and NF-κB in model group were higher than those of sham-operated group respectively (P<0.01). The protein expressions of p-p38 and NF-κB in sham-operated group were not apparent.Conclusion:Shentongzhuyu decoction can delay lumbar disc degeneration, and the probalble mechanism is related to down-regulating the expression of p-p38 and NF-kB and inhibiting the activation of p38MAPK signal pathway.